Gregarious flowering and death of understorey bamboo slow litter decomposition and nitrogen turnover in a southern temperate forest in Patagonia, Argentina - Austin, Amy Theresa (2011)
1. The massive synchronized flowering and subsequent mortality of understorey bamboo species occur in infrequent and unpredictable intervals in temperate and subtropical forests around the world. Because of the sporadic occurrence of these flowering episodes and the long intervals between events, very little is known about their consequences on biogeochemical cycling in natural ecosystems. 2. In 2001, a synchronized flowering and dieback of the native bamboo, Chusquea culeou E. Desv., occurred, covering more than 200 000 ha in the north-west region of Patagonia, Argentina. We explored the impacts of this gregarious flowering event on litter decomposition and nitrogen turnover in an old-growth southern beech forest for 3 years after the flowering event. 3. Bamboo litter decomposed significantly slower than overstorey tree litter, and decomposition in flowered patches overall was significantly reduced compared to remnant live understorey patches. In addition, soil mineral nitrogen was reduced in flowered patches, and nitrogen transformations were altered, most notably in the third year after the flowering event. 4. This infrequent phenomenon of gregarious flowering could have consequences for carbon and nutrient cycling, as low-quality standing dead biomass is gradually incorporated into soil organic matter pools. This study demonstrates that large biotically mediated perturbations of understorey vegetation can impact biogeochemical cycles in temperate forest ecosystems by reducing carbon turnover and altering nitrogen availability and transformations, even in the absence of physical disturbance.